Comparative study of attitude towards research, academic motivation, goal orientation and attributional styles in nursing and educational sciences students - Alcalá-Albert, Gregorio Jesús; Parra-González, María Elena (Edelweiss Applied Science and Technology, 2025)
In recent years, the number of doctoral theses has decreased, a fact that jeopardises the progress of such important disciplines as education and health, which are also fundamental human rights. It is important to know the interest and its attributions in students; Methods: An observational, descriptive, correlational and cross-sectional study was carried out using the EACIN and CEAP-48 scales; Results: A total of 429 individuals participated. Age influenced research interest, decreasing as the individual grew older. Interest between genders did not show significant differences, however, the female gender showed a greater relationship with motivation. Students from public universities significantly related interest to motivation and those from private universities also related interest to performance. Conclusions: the students of both sciences show neutral values of interest in research that are directly related to academic motivation, making it necessary to know the teaching methodologies used by the teaching staff for their teaching, which is essential to respond to future social needs.